Difficulties in understanding the autonomy of science: consequences of state sovereignty - Musielewicz, Michael P. (Hybris, 2016)
The importance of the autonomy of science is generally assumed to be good for the proper functioning of science. Yet, when we examine the notion more closely, various difficulties present themselves and cloud our understanding of this important concept. One such complication presents itself when we examine the relationship between science and the state. When examining the relationship between science and the state, there is an area of overlap that is called by Alvin Weinberg as trans-science. This concept contains within it an axiology of science that has bearing upon the scientific process itself. This leads us to ask, who determines the values in this axiology of science? In this paper I will argue that the state takes precedence in determining these values in the axiology of science which impacts science’s autonomy. To do this, I will first present an outline of what the concept of trans-science is. Next I will present the axiology of science and ways of determining it. Finally I will present the State’s role in determining these values.